Historical transmission of stereotypes in the elite’s sensationalism, Case study: ‘The Most Powerful Women of Valle del Cauca, Colombia’ - Tusa Jumbo, Fernanda; Briceño Castillo, Xavier; Tusa Jumbo, Eduardo (Estudios sobre el Mensaje Periodístico, 2017)
The present academic work does an analytical study of a picture published in 2011 by Hello Magazine under the title “Women most powerful of Valle del Cauca (Colombia), in the amazing Hollywood mansion of Sonia Zarzur in the Beverly Hills of Cali ‘. In that sense, the sensational topic is recurrent under variables such as ‘discrimination’, ‘racism’, ‘elite’ and ‘tradition’. To this point, this paper uses the methodology of qualitative content analysis and bibliographic and documentary review. We conclude that sensationalism is historically a common resource inside mass media. We recommend the use of media literacy, with the objective to not invisible or violate the human rights of social groups, such as the case study of black Colombian women